Characteristics of Spatial Rainfall Distribution in North-East Thailand - Kingpaiboon, Sununtha (Engineering and Applied Science Research, 2013)
Daily Rainfall data is provided by 134 stations located in North-east Thailand courtesy of the Department of Meteorology of Thailand. The longest period of data records for the main station of each province dates from 1951. This paper presents the preliminary analysis of spatial rainfall distribution and long-term variability in this region. The annual mean rainfall within the period of records for each station were analyzed. They varied from 777.4 mm. at Kaset Sombun (Chaiyaphum province) to 2808.4 mm. at Bungkan (Nonh Khai province). These data were input to Geographic Information System and were manipulated to create contours of rainfall and classified to a surface of rainfall distribution. The results showed that the amount of rainfall in the West, and South-west is 700-1200 mm. at Chaiyaphume, Nakhon Ratchasima, Khon Kaen and progressively increases to the North-east, and East, where the maximum rainfall is greater than 2000 mm. at Nong Khai, Nakorn Phanom. The long-term inter annual variability of rainfall for the main stations of 13 provinces for the period 1951-1998 were analyzed and it was found that the trends of rainfall mostly decrease in this region but increase for the areas of Loei and Sakon Nakhon provinces.